Integrated modeling of telescopes - Andersen, T. (Torben) 1954- (Astrophysics and space science library, 2011)
With increasingly complex and costly opto-mechanical systems, there is a growing need for reliable computer modeling and simulation. The field of integrated modeling, combining optics, mechanics, control engineering, and other disciplines, is the subject of this book. Although the book primarily focuses on ground-based optical telescopes, the techniques introduced are applicable also to other wavelengths and to other opto-mechanical applications on the ground or in space. Basic tools of integrated modeling are introduced together with concepts of ground-based telescopes. Modeling of optical systems, structures, wavefront control systems with emphasis on segmented mirror control, and active and adaptive optics are described together with a variety of noise sources; many examples are included in this book. Integrated Modeling of Telescopes is a text for physicists and engineers working in the field of opto-mechanical design and wavefront control, but it will also be valuable as a textbook for PhD students.